2024
DOI: 10.21608/edj.2023.234643.2710
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Shaping Ability of Three Rotary Systems in Primary Molars: In Vitro Study

Sarah khalil,
sara elmallah,
Ahmed Negm

Abstract: Aim: This in-vitro study aimed to evaluate the shaping ability of hand K files, Kedo S, Hyflex, and the Race evo rotary files when used in the biomechanical preparation of primary molars by using CBCT. Materials and methods:One hundred forty extracted human primary mandibular second molars were randomly allocated into 4 groups of 35 each. Group A: Prepared with stainless steel hand files (MANI, Inc.; Tochigi, Japan), group B: Prepared with Kedo S plus pediatric rotary files (Chennai, Tamil Nadu, India), group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The present study findings partially rejected the null hypothesis as there was a highly significant statistical difference regards the removed dentin amount on both mesial & distal sides between the three groups at the cervical & apical thirds, whereas a non-significant difference was observed at the middle third (null hypothesis was accepted). These results could be related to variations in the file design, the degree of root canal curvature, instrumentation procedures, and the number of files [ 28 ]. This was in contrast with Abd El-Fatah et al [ 10 ] study in which a non-significant statistical difference was found concerning the amount of dentin removed at the coronal & apical thirds among hand K-file, Fanta, and Zuanba groups while a significant difference was present at the middle third ( P = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…The present study findings partially rejected the null hypothesis as there was a highly significant statistical difference regards the removed dentin amount on both mesial & distal sides between the three groups at the cervical & apical thirds, whereas a non-significant difference was observed at the middle third (null hypothesis was accepted). These results could be related to variations in the file design, the degree of root canal curvature, instrumentation procedures, and the number of files [ 28 ]. This was in contrast with Abd El-Fatah et al [ 10 ] study in which a non-significant statistical difference was found concerning the amount of dentin removed at the coronal & apical thirds among hand K-file, Fanta, and Zuanba groups while a significant difference was present at the middle third ( P = 0.043).…”
Section: Discussionmentioning
confidence: 99%